Stable isotope analyses on archived fish scales reveal the long‐term effect of nitrogen loads on carbon cycling in rivers. (23rd August 2013) - Roussel, Jean‐Marc; Perrier, Charles; Erkinaro, Jaakko; Niemelä, Eero; Cunjak, Richard A.; Huteau, Dominique; Riera, Pascal
Abstract Stable isotope analysis of organic matter in sediment records has long been used to track historical changes in productivity and carbon cycling in marine and lacustrine ecosystems. While flow dynamics preclude stratigraphic measurements of riverine sediments, such retrospective analysis is important for understanding biogeochemical cycling in running waters. Unique collections of riverine fish scales were used to analyse δ15N and δ13C variations in the food web of two European rivers that experience different degrees of anthropogenic pressure. Over the past four decades, dissolved inorganic N loading remained low and constant in the Teno River (70°N, Finland); in contrast, N loading increased fourfold in the Scorff River (47°N, France) over the same period. Archived scales of Atlantic salmon parr, a riverine life‐stage that feeds on aquatic invertebrates, revealed high δ15N values in the Scorff River reflecting anthropogenic N inputs to that riverine environment. A strong correlation between dissolved inorganic N loads and δ13C values in fish scales was observed in the Scorff River, whereas no trend was found in the Teno River. This result suggests that anthropogenic N‐nutrients enhanced atmospheric C uptake by primary producers and its transfer to fish. Our results illustrate for the first time that, as for lakes and marine ecosystems, historical changes in anthropogenic N loading can affect C cycling in riverine food webs, and confirm the long‐term interactions between N and C biogeochemical cycles in running waters.